Tingkat Pendidikan Orang Tua Dan Prestasi Belajar Siswa Dalam Bidang Studi Bahasa Indonesia Kelas VIII SMP Negeri 4 Sragen Tahun Pelajaran 2011/2012 - Listyarini, Dewi; , Prof. Abdul Ngalim; , Drs. Andi Haris Prabawa, M.Hum (2017)
There are three objectives of this study that will be discussed. 1) The relationship of education Parents who are low, middle, high. 2) Describe the relationship Parental education on learning achievements in language studies Indonesia. 3) know the degree of correlation of parental education level to Student achievement in the field of study of Indonesian language. This research Using a quantitative approach. Data collection techniques Used documentation and questionnaires. Research population of all students of the class VIII SMP Negeri 4 Sragen which amounted to 190 students, the sample amounted to 113. The level of education of parents of students in SMP Negeri 4 Sragen mostly Educated at senior high school level as many as 45 people or (39.8%), junior high school 38 Students or (33.6%), SD 21 people or (18.6%), PT was ranked The lowest with a total of 9 people or (8.0). Student achievement in the field Indonesian studies are mostly moderately good performers (moderate) Ie as many as 62 people or (54.9%). Test multicolonierity 0.339 hypothesis test Done by using statistical analysis of square test The level of parent education and student achievement in the field of study Indonesian language based on chi square test is known P = 0,022 <0,05 Shows a positive and significant relationship. The data Obtained from the analysis with a significant level of 0.05. Keywords: Student's parents, learni